Critical discourse analysis of Obama’s and Trump’s speeches using Halliday And Hassan’s lexical cohesive theory - Fariha Bibi (Indonesian Reseacher for Language Learning and Teaching, 2024)
In everyday life, humans create text while speaking or writing, which is considered a tool of communication. Speech is the verbal form of communication that helps people interact with each other, convey information, and influence and encourage people to take certain actions. Cohesion is a key element in both spoken and written text construction that helps the reader or listener grasp the information by making it productive and logical. This study tries to identify different kinds of lexical cohesion devices used in the speeches of Trump and Obama. Obama's and Donald’s speeches text aided as the main source of data for this qualitative descriptive study, which focused on the lexical cohesion theory presented by Halliday and Hasan 1976. After data analysis, the researcher found various lexical cohesive devices in the speeches such as repetition, synonym, superordinate, general word, and collocation. In both speeches, repetition is one of the most used lexical devices and general words are the least used. In Obama’s speech repetition contains 75% and general words 2% while in Donald’s 34% and 4% respectively. Repetition helps the speakers to make the argument stronger. These strategies were employed to help the audience to comprehend perfectly what was said.